La Situation Des Enfants En Dehors Du Systeme Scolaire En Côte d’Ivoire - Lazare, Sika Glebelho; Elise, Kacou Amoin (European Scientific Journal, ESJ, 2018)
One of the goals of Education for All (EFA) was to ensure that by 2015 children, specifically girls, vulnerable children and those belonging to ethnic minorities, have access to compulsory and free quality primary education and follow it to completion. However, at the end of 2015, Ivory Coast had not been able to achieve the objectives set, particularly the universal schooling of children and adolescents. The country faces many constraints related to its education system, notably school exclusion. The problem of access and maintenance of children in the system, whether they relate to the demand for or supply of education, remain important. The 2002 political crisis has exacerbated the obstacles to children’s schooling because of the massive displacement of populations and the lack of infrastructures. What are the main factors behind school exclusion? how many children and adolescents are out of school? what are the economic implications? To answer these questions, we rely on data from the national survey of out of school children and adolescents conducted in 2015. The study reveals that 1,550,586 children aged 3-5; 1,123,674 children aged 6-11, 797 137 of 12-15 years are out of the school system. In order to achieve economic emergence, the country must imperatively address the problem of access to education with the utmost speed.